2007
DOI: 10.1088/0953-8984/19/45/456210
|View full text |Cite
|
Sign up to set email alerts
|

First principle calculations of molecular polarization switching in P(VDF–TrFE) ferroelectric thin Langmuir–Blodgett films

Abstract: This paper reports first principle calculations and analysis of the molecular mechanism of the polarization switching in polyvinylidene fluoride and its copolymer with trifluoroethylene (P(VDF–TrFE)) using semi-empirical and ab initio quantum chemical methods based on the HyperChem 7.5 and Gaussian98 programs. The simulations were performed for different copolymer contents in P(VDF–TrFE)—(70:30), (60:40) and pure PVDF. The calculated values of the dipole moment and average polarization of the molecular chains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 30 publications
4
27
0
13
Order By: Relevance
“…These studies continue the series of our previous investigations of ferroelectric and nanoscale properties of thin LB PVDF copolymer films [8,[16][17][18][19][20][21]. The analysis of computational and experimental data and new computed evaluations obtained allow us to estimate the sizes of possible transition region approximately to be of the order of 10 nm.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…These studies continue the series of our previous investigations of ferroelectric and nanoscale properties of thin LB PVDF copolymer films [8,[16][17][18][19][20][21]. The analysis of computational and experimental data and new computed evaluations obtained allow us to estimate the sizes of possible transition region approximately to be of the order of 10 nm.…”
Section: Introductionsupporting
confidence: 64%
“…Computational studies of the polarization switching mechanism in such polymer films were performed on an idealized model, consisting of one, two and four polymer chains with limited structural units by means of the first-principles quantum theory [15][16][17][18][19][20][21].…”
Section: Intrinsic Homogeneous Polarization Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…First principle calculations by Bystrov et al have shown that interaction between molecular chains of PVDF leads to the orientation of each molecular dipole moment along one direction parallel to the chain plane. [35] It is noteworthy that although β-phase crystals do not have preferential orientation in PVDF films formed by phase inversion 15 or by drying in air; 12 the PVDF membranes obtained may still exhibit a certain degree of piezoelectric effect as shown by our results in Figure 3h. However, this aspect has been largely ignore in the literature with the porous PVDF films formed by phase inversion usually considered unsuitable for poling and electroactive applications.…”
mentioning
confidence: 60%
“…As water is a dipolar molecule, the electric field acts on the initial surface, inducing aligned -crystals, which in turn causes the alignment of the -phase crystals in the sequential crystallisation. Using first-principle calculations, Bystrov et al have shown that the interaction between PVDF molecular chains leads to the orientation of each molecular dipole moment along one direction parallel to the chain plane [36]. On the other hand, the molecular interaction in PVDF will lead to the same orientation direction as ZnO growth direction [22], thus they increase the charge density more profoundly, hence increasing the overall efficiency of TENG devices.…”
Section: Mechanism For Performance Enhancement Of Tengsmentioning
confidence: 99%